The Implementation of Waiters And Waitresses’ Upselling Techniques At Ticket’s Cafe of Horison Ultima Makassar Hotel - Dewi Andriani; Riska Veronika; Nila Sartika Achmadi (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2020)
This study aims to analyze the use of upselling techniques among waiters and waitresses at the Ticket’s Café in Hotel Horison Ultima Makassar. This analysis includes the answer to whether or not they use upselling techniques, how they use it, and what the result is. The data in this research are collected during observation and interview. This research studies the waiters and waitresses along with their superiors. The data are then analyzed with descriptive qualitative method which includes data reduction, presentation and conclusion drawing. The result of this research is that the waiter and waitresses have been proven to use some upselling techniques; however the implementation is not as effective as expected because the number of waiters and waitresses is not enough to deliver the best impacts of the techniques and not all of them use the right upselling techniques.